2017
DOI: 10.1080/17476348.2017.1389277
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial function in patients with chronic obstructive pulmonary disease: a systematic review of studies using flow mediated dilatation

Abstract: This review provides evidence for impaired peripheral endothelial function in COPD. Since impaired endothelial function may contribute to cardiovascular morbidity, a more comprehensive cardiovascular phenotyping is considered important in COPD to address cardiovascular risk. A high frequency of cardiovascular comorbidity is observed in COPD patients, and therefore well-controlled, larger studies that investigate endothelial function in COPD patients are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 56 publications
2
27
2
2
Order By: Relevance
“…The difference in strength of associations between the sexes was unexpected. It is not known whether this sex difference would be found in older cohorts or those with established lung or cardiovascular disease: most previous reports on associations between endothelial function and respiratory diseases comprise relatively smaller samples of older men and women and, as far as we are aware, none have investigated sex differences . We can only speculate on the reasons for this effect modification by sex.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The difference in strength of associations between the sexes was unexpected. It is not known whether this sex difference would be found in older cohorts or those with established lung or cardiovascular disease: most previous reports on associations between endothelial function and respiratory diseases comprise relatively smaller samples of older men and women and, as far as we are aware, none have investigated sex differences . We can only speculate on the reasons for this effect modification by sex.…”
Section: Discussionmentioning
confidence: 81%
“…It is not known whether this sex difference would be found in older cohorts or those with established lung or cardiovascular disease: most previous reports on associations between endothelial function and respiratory diseases comprise relatively smaller samples of older men and women and, as far as we are aware, none have investigated sex differences. 2,[6][7][8][9][10][11][12][13] We can only speculate on the reasons for this effect modification by sex. There are established, but poorly understood, sex differences in the associations between lung function and other systemic conditions: previous research in this cohort has identified several sex interactions between lung function and non-respiratory health.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, the discrepancies in the findings may be attributed to the fact that: 1) our study only excluded COPD patients with other pulmonary conditions, rapid lethal disease and severe immunosuppression and therefore affords a more reasonable representation of the general COPD population, while, on the other hand, Malerba et al [33] excluded patients with a history of any cardiovascular disease except arterial hypertension, diabetes mellitus and if the patient had an exacerbation in the previous 6months; and 2) in the study of Malerba et al [33], patients had less severe COPD than the patients in our study. In a number of studies, both FMD and RHI are lower in COPD patients than in controls, but the association with COPD parameters is tenuous [45,46]. Eickhoff et al [10] found an association between FMD and FEV 1 % predicted in a univariate analysis, but no significant association between FMD and GOLD status.…”
Section: Discussionmentioning
confidence: 99%